Between the ghetto and the establishment: Bobi Wine, Uganda’s NUP and the challenges of movement-to-party transition in an electoral autocracy - Kristof Titeca; Anders Sjögren; Frank Ahimbisibwe (The Journal of Modern African Studies, 2025)
What does the institutionalisation of a protest movement into an opposition party in an electoral autocracy mean for its members? This article examines this question by analysing the conversion of People Power, a political pressure group in Uganda, into the National Unity Platform (NUP), focusing on the dilemmas of organisation, strategy and identity. NUP sought to broaden and institutionalise People Power’s activities to be seen as a credible party capable of holding state power. Simultaneously, its initial political weight was closely tied to the defiant, extra parliamentary energy of the grassroots – a resource the party needed to preserve. These tensions were intensified by Uganda’s authoritarian context, where state repression and demobilisation intersected with uneven access to resources and patronage, producing frictions between privileged actors and grassroots members. The paper shows how these dilemmas generated frustrations among bottom-up constituencies and highlights the importance of examining intraparty processes from a grassroots perspective.
Keywords: Uganda; opposition; protest movement; Bobi Wine; electoral autocracy